2010
DOI: 10.1159/000313897
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Transcriptional Profiling of Chemical-Stimulated Dendritic Cells Identifies Immunogenic Contact Allergens, but Not Prohaptens

Abstract: Allergic contact dermatitis is a complex syndrome and knowledge about the in vitro detection of small-molecular-weight compounds, particularly prohaptens, is limited. Therefore, we investigated chemical-induced gene expression changes in human antigen-presenting cells upon stimulation with immunogenic contact allergens, prohaptens and irritants. Monocyte-derived dendritic cells (moDCs) and THP-1 cells were stimulated with the prohapten cinnamic alcohol (CAlc), the hapten cinnamic aldehyde (CAld), an irritant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…Human primary dendritic cells as well as myeloid cell lines are used in in vitro approaches to predict skin sensitization (Basketter et al, 2008;Ott et al, 2010;Python et al, 2009), e.g., the Myeloid U937 Skin Sensitization Test (MUSST), which measures increase of CD86 expression (Ade et al, 2006;Python et al, 2007), the human Cell Line Activation Test (h-CLAT), which assesses increase of CD86 and combined CD54 expression (Sakaguchi et al, 2006), or the Genomic Allergen Rapid Detection (GARD), which is based on a signature of predictive genes differentially regulated in the MUTZ3 cell line when stimulated with sensitizing compared to non-sensitizing compounds (Johansson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human primary dendritic cells as well as myeloid cell lines are used in in vitro approaches to predict skin sensitization (Basketter et al, 2008;Ott et al, 2010;Python et al, 2009), e.g., the Myeloid U937 Skin Sensitization Test (MUSST), which measures increase of CD86 expression (Ade et al, 2006;Python et al, 2007), the human Cell Line Activation Test (h-CLAT), which assesses increase of CD86 and combined CD54 expression (Sakaguchi et al, 2006), or the Genomic Allergen Rapid Detection (GARD), which is based on a signature of predictive genes differentially regulated in the MUTZ3 cell line when stimulated with sensitizing compared to non-sensitizing compounds (Johansson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that NQO1 induction occurs via AhR-dependent Nrf2 activation (Haarmann-Stemmann et al, 2012). Ott et al (2010) and Python et al (2009) have identified NQO1 as a marker gene up-regulated after stimulation of moDCs with cinnamic aldehyde by microarray analysis. NQO1 was modulated by most sensitizers after exposure of MUTZ-3 cells and PBMDCs (peripheral blood mononuclear-derived dendritic cells) with selected sensitizers for 24 h (Python et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ambion® WT Expression Kit (Ambion, Kaufungen, Germany) was used to generate purified sense-strand cDNA with incorporated dUTP according to the technical manual. Fragmentation and labeling was done using the Affymetrix Gene Chip WT Terminal Labeling kit (Affymetrix, Santa Clara, Calif., USA) according to the manufacturer’s recommendations [15]. Each sample was hybridized to a Gene Chip Human Exon 1.0 ST array for 16 h at 45°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies revealed that ABC transporters not only have a protective function related to their capacity to extrude toxic compounds but also have additional regulatory functions of these transport systems on immune cells (Ott et al, 2010). the multidrug resistance related proteins (MRP, gene name: AtP-binding cassette C transporters, ABCC) are a subfamily of ABC transporters and consist of at least seven members.…”
Section: Qualitative and Quantitative Allergen-specific Protein Profimentioning
confidence: 99%